EVALUATION OF NEUTRON SCATTERING CORRECTION USING THE SEMI-EMPIRICAL METHOD AND THE SHADOW-CONE METHOD FOR THE NEUTRON FIELD OF THE KOREA ATOMIC ENERGY RESEARCH INSTITUTE. Issue 1 (19th October 2017) - Lee, Seung Kyu; Kim, Sang In; Lee, Jungil; Chang, Insu; Kim, Jang-Lyul; Kim, Hyoungtaek; Kim, Min Chae; Kim, Bong-Hwan
Abstract: When neutron survey metres are calibrated in neutron fields, the results for room- and air-scattered neutrons vary according to the distance from the source and the size, shape and construction of the neutron calibration room. ISO 8529-2 recommends four approaches for correcting these effects: the shadow-cone method, semi-empirical method, generalised fit method and reduced-fitting method. In this study, neutron scattering effects are evaluated and compared using the shadow-cone and semi-empirical methods for the neutron field of the Korea Atomic Energy Research Institute (KAERI). The neutron field is constructed using a 252 Cf neutron source positioned in the centre of the neutron calibration room. To compare the neutron scattering effects using the two correction methods, measurements and simulations are performed using respectively KAERI's Bonner sphere spectrometer (BBS) and Monte Carlo N-Particle code at twenty different positions. Neutron spectra are measured by a europium-activated lithium iodide [ 6 LiI(Eu)] scintillator in combination with the BBS. The calibration factors obtained using each methods show good agreement within 1.1%.